Association of GRACE Risk Score with Angiographic Severity of Coronary Artery Disease in patients with ST Elevation Myocardial Infarction - Saha, Tapash; Khalequzzaman, Md; Akanda, Md Abdul Kader; Saha, Simu; Tushar, Asif Zaman; Ahmed, Rashid; Saha, Gouranga Kumar; Ullah, Mohammad (Cardiovascular Journal, 2015)
Background: Clinical guidelines recommend that optimal management of acute coronary syndrome should include patient risk stratification. Predicting the anatomical extension of coronary artery disease is also potentially useful for clinical decision. The objective of our study is to determine whether the GRACE risk score correlates with the angiographic extent and severity of coronary artery disease in patients with ST elevation myocardial infarction. Methodology: 50 patients diagnosed with Acute Myocardial Infarction were included as sample by purposive sampling method. GRACE risk score for each patient was calculated and the patients were divided into groups according to the GRACE risk score: low risk (<108); intermediate risk (109-140). The severity of the coronary artery disease was assessed by vessel score and Gensini score. Relation between Grace score and Gensini score was evaluated. Results: Mean GRACE score of study population was 128.3±22.7. Mean Gensini score was 23.88±17. Mean Gensini score were 15.47±10.4, 27.75±9.26 and 31.52±16.91 in low GRACE risk group, intermediate group and high risk group respectively and the difference of mean Gensini score was statistically significant (p=0.006). In our study correlation co-efficient between GRACE risk score and Gensini score was r=0.17 (p=0.04). Multiple regression analysis showed that age more than 50 years (p=0.02), ST segment deviation (p=0.01), smoking (p=0.02), hypertension (p=0.01) were able to independently predict patients with severe CAD. Conclusion: Our study demonstrates that the GRACE risk score carries a significant positive correlation with the coronary artery disease severity in patients with STEMI. Cardiovasc. j. 2015; 8(1): 30-34